1999
DOI: 10.1016/s0002-9440(10)65454-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Hybridization Analysis of Natural Killer Cell Lymphoma/Leukemia

Abstract: Putative natural killer (NK) cell lymphoma/leukemia is a rare group of recently characterized hematolymphoid malignancies. They are highly aggressive and frequently present in extranodal sites, including the nasal area and the upper aerodigestive system, and nonnasal areas such as the skin and the gastrointestinal tract. According to clinicopathological features, they can be classified into nasal NK cell lymphoma, nasal-type NK cell lymphoma occurring in nonnasal areas, and NK cell lymphoma/leukemia. Genetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
3
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(101 citation statements)
references
References 26 publications
6
90
3
2
Order By: Relevance
“…10,11,13,14 Nevertheless, 6p21 amplification is unlikely to be specific for FL, since it has been also reported in 6% of diffuse large B-cell NHLs, 12 in 13% of primary gastric NHLs 25 and in 30% of NK NHL/leukemias. 26 Using probes specific for the centromeric region and the long arm of the chromosome 6, we found that one case showed a pattern highly suggestive for the presence of an isochromosome 6p. This aberration is very common in human retinoblastoma, 27 but has also been reported in approximately 1% of acute lymphoblastic leukemia 28 and Hodgkin's lymphoma 29 and in 6% of primary mediastinal 30 and gastric NHLs, 25 as well as in individual cases of follicular, 10 nodal diffuse large B-cell 31 and nasal T/NK NHLs 32 and of Waldenstrom's macroglobulinemia.…”
Section: Discussionmentioning
confidence: 88%
“…10,11,13,14 Nevertheless, 6p21 amplification is unlikely to be specific for FL, since it has been also reported in 6% of diffuse large B-cell NHLs, 12 in 13% of primary gastric NHLs 25 and in 30% of NK NHL/leukemias. 26 Using probes specific for the centromeric region and the long arm of the chromosome 6, we found that one case showed a pattern highly suggestive for the presence of an isochromosome 6p. This aberration is very common in human retinoblastoma, 27 but has also been reported in approximately 1% of acute lymphoblastic leukemia 28 and Hodgkin's lymphoma 29 and in 6% of primary mediastinal 30 and gastric NHLs, 25 as well as in individual cases of follicular, 10 nodal diffuse large B-cell 31 and nasal T/NK NHLs 32 and of Waldenstrom's macroglobulinemia.…”
Section: Discussionmentioning
confidence: 88%
“…To compare our findings with previous published data, we assembled all CGH data through an extensive literature search [4][5][6][7][8][9][10][11]21 that included three studies: conventional CGH on 9 Korean patients, 4 conventional CGH on 10 Chinese patients 8 and aCGH on 27 Japanese patients. 6 We also included other reports with cytogenetics, loss of heterozygosity (LOH) and fluorescent in situ hybridization data on 15 cases of NK-cell malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies of genome-wide alterations have been published on NK-cell malignancies [4][5][6][7][8][9][10][11] due to the rarity of this entity and the difficulty in obtaining adequate biopsy specimens. Therefore, well-characterized NK cell lines, supplemented with tumor specimens, can have an important role in the investigation of NK-cell malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…So far, no other genetic alterations (e.g. ITK-SYK translocation [52], IRF4 rearrangements [53], abnormalities, or deletions in chromosome 6q, 7q, or 9q [5456]) have been linked to diagnosis, complicating clinical decisions in the treatment of PTCL patients. Moreover, combined chemotherapy (CHOP; Cyclophosphamide, Doxorubicin, Vincristine, Prednisolone; or CHOEP with Etoposide) often results initially in favorable response rates, however relapses and refractory disease are frequently observed [45,57].…”
Section: Targets In Ptcl and Driver Mutationsmentioning
confidence: 99%